Locoregional failure after postoperative flank irradiation for nephroblastoma: Results from the French cohort of the SIOP‐2001 trial. Issue 12 (4th September 2022) - Jouglar, Emmanuel; Laprie, Anne; Isfan, Florentina; Dumont, Benoit; Thebaud, Estelle; Escande, Alexandre; Supiot, Stéphane
Abstract: Objective: To describe locoregional failure (LRF) after postoperative flank radiotherapy (RT) among French patients with nephroblastoma included in the Société Internationale d'Oncologie Pédiatrique (SIOP)‐2001 protocol. Patients and methods: In selected SIOP‐2001 patients, planning with simulation computed tomography (CT) scan and posttreatment CT scan demonstrating LRF were registered and analyzed. LRF was contoured and classified as in‐field, marginal or out‐of‐field according to dose distribution. Results: Total 316 French SIOP‐2001 patients were treated with postoperative RT. Three patients with nephroblastoma developed LRF after flank RT. All failures were located within the retroperitoneum. In two patients, the relapse was within the RT field and in one it was classified as marginal. Conclusion: LRF after postoperative flank RT for nephroblastoma was rare and exclusively situated in the retroperitoneum. These results point out this region as the most at risk of local relapse. A prospective evaluation of a target volume restricted to the retroperitoneum allowing the use of modern and highly conformal radiation techniques in order to decrease dose to normal tissues shall be encouraged.